Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1988
DOI: 10.1115/88-gt-133
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Sodium Sulfate Mass Transfer and Low-Temperature Hot Corrosion

Abstract: A mass transfer model is developed that considers diffusive and chemical aspects of sodium sulfate formation and deposition on cooled blades of coal-fired gas turbines. The roles of gas phase condensation of sodium sulfate and multicomponent diffusion across a chemically frozen thin boundary layer are elaborated. A rational procedure is presented for correlating material wastage with laboratory weight gain data obtained by exposing alloy specimens pre-coated with a thin film of salt to SO2-SO3 in an oxygen env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…For years, corrosion problems associated with molten Na 2 SO 4 have been studied in isolation with the gas turbines. The chemistry involved during the formation of Na 2 SO 4 becomes highly complex in a coal or syngas fired gas turbine as discussed by Ahluwalia and co-researchers [5,6]. Sodium, as an impurity in coal, exists primarily as a halide, alumino-silicate or in combination with the organic matter.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…For years, corrosion problems associated with molten Na 2 SO 4 have been studied in isolation with the gas turbines. The chemistry involved during the formation of Na 2 SO 4 becomes highly complex in a coal or syngas fired gas turbine as discussed by Ahluwalia and co-researchers [5,6]. Sodium, as an impurity in coal, exists primarily as a halide, alumino-silicate or in combination with the organic matter.…”
Section: Introductionmentioning
confidence: 96%
“…This paper explores the validity of this assumption. Present study uses the results reported by Ahluwalia and Im [6] along with a simple resistance model for heat and mass transfer to establish the variation of hot corrosion rate along a surface, in the presence of film cooling for various film effectiveness distributions corresponding to different blowing ratios. The paper then identifies whether LTHC gets suppressed or augmented in the presence of film cooling.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations